Philippine medical thesaurus on diseases skin and connective tissue diseases and neonatal diseases and abnormalities, in Tagalog - Chavez, Loren G. (2002)
The field of medicine is always associated with diseases and abnormalities. Medical terms are largely focused on foreign languages, especially American English, in describing and naming majority of ailments and medical operations. The consequence is that common people cannot completely comprehend medical terms regarding diseases they may have acquired or heard.